Gejala Psikotik pada Pasien dengan Epilepsi Tidak Terkontrol - High Boy Karmulrubog Hutasoit; Osy Lu’lu Alfarossi (CV. Jasa Sukses Abadi, 2020)
Five until six percents patients with chronic uncontrolled epilepsy have shown with psychotic symptoms and increase eightfold risk for schizophrenia, especially temporal lobe epilepsy. Even the mechanisme still unknown, however family history, early onset epilepsy, and seizure type are the predictors of pshychotic in epilepsy. A 29-year-old man hospitalized after raged and destroyed neighbour’s house. The patient has history of uncontrolled epilepsy for 10 years and psychotics syndrome 1 year after the first seizure. In the psychiatricus status obtained dirty and untidy appearance, cooperative, dysphoric mood, flat affect, auditory, visual, and tactile hallucinations, paranoid delution, poor cognitive, and insight degree one. The multiaxial diagnosis with axis I: other determined mental disoder caused by brain damage and dysfunction and other illness, axis II: have not diagnose yet, axis III: idiopathic general epilepsy and epileptic syndrome, axis IV: economic, family, and social environment problems, and axis V: GAF 60-51. The patient treated with oral haloperidol 2x1,5 mg, oral tryhexiphenidil 2x2 mg, oral chlorpromazine 1x50 mg, oral phenitoin 1x100 mg, and oral depakote 1x250 mg. The patient got discharged after 21 days care with no auditory, visual, and tactile hallucinations.